APC Resistance and other Haemostatic Variables during Pregnancy and Puerperium - Kjellberg, U.; Andersson, N.-E.; Rosén, S.; Tengborn, L.; Hellgren, M. (Thrombosis and Haemostasis, 1999)
Forty-eight healthy pregnant women were studied prospectively and longitudinally. Blood sampling was performed at 10-15, 23-25, 32-34 and 38-40 weeks of gestation, within one week and at eight weeks postpartum. Classic and modified activated protein C ratio decreased as pregnancy progressed. In the third trimester 92% of the ratios measured with the classic test were above the lower reference level whereas all modified test ratios were normal. Slight activation of blood coagulation was shown with increased levels of prothrombin fragment 1+2, soluble fibrin and D-dimer. Fibrinogen, factor VIII and plasminogen activator inhibitor type 1 and type 2 increased. Protein S and tissue plasminogen activator activity decreased. Protein C remained unchanged. No correlation was found between the decrease in classic APC ratio and changes in factor VIII, fibrinogen, protein S, prothrombin fragment 1+2 or soluble fibrin, nor between the increase in soluble fibrin and changes in prothrombin fragment 1+2, fibrinogen and D-dimer.